1997
DOI: 10.1079/bjn19970027
|View full text |Cite
|
Sign up to set email alerts
|

Food intake and diet selection in sheep: the effect of manipulating the rates of digestion of carbohydrates and protein of the foods offered as a choice

Abstract: An experiment was designed to investigate whether the degree of synchrony between the rates of digestion of carbohydrates and N of foods offered as a choice would have an effect, through their consequences, on the short-and long-term diet selection of sheep. Four foods (RL, RH, SL and SH) with the same high metabolizable energy, and similar high metabolizable protein contents were made into pellets. Foods RL and RH were based on a rapidly fermentable carbohydrate source and foods SL and SH on a slowly fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 16 publications
1
13
1
1
Order By: Relevance
“…Therefore, the environmental temperature probably had a similar affect on the intakes of dry matter, feed ingredients and nutrients of TMR-and FCF-fed lambs in the present study. High dietary protein or energy concentration in fattening lamb diets may result in the occurrence of digestive disturbance (Kyriazakis and Oldham, 1997), abnormal or erratic feeding behaviour (Askar et al, 2006;Favreau et al, 2010). In the present study, no occurrence of these problems in FCF-fed lambs was observed probably due to the fact that TMR-and FCF-fed lambs had a similar crude fibre intake.…”
Section: Resultsmentioning
confidence: 44%
See 1 more Smart Citation
“…Therefore, the environmental temperature probably had a similar affect on the intakes of dry matter, feed ingredients and nutrients of TMR-and FCF-fed lambs in the present study. High dietary protein or energy concentration in fattening lamb diets may result in the occurrence of digestive disturbance (Kyriazakis and Oldham, 1997), abnormal or erratic feeding behaviour (Askar et al, 2006;Favreau et al, 2010). In the present study, no occurrence of these problems in FCF-fed lambs was observed probably due to the fact that TMR-and FCF-fed lambs had a similar crude fibre intake.…”
Section: Resultsmentioning
confidence: 44%
“…A higher the daily weight gain may be related to the amounts of ingested protein and energy in the FCF systems was theoretically in excess of nutrient requirements for fattening (NRC, 2007) due to the fact that the FCF system increased the dry matter, energy and protein intakes (Tables 2 and 4). Many factors, such as inherent characteristics of the animal and long-or short-term environmental and managemental conditions have been reported to affect diet selection and behavioral responses as well as fattening performance (Kyriazakis and Oldham, 1997;Sahin et al, 2003;Kaya et al, 2011). Kaya (2011) reported that the performance of lambs in outdoor in hot climate condition could be inferior to that of lambs in a more controlled environment because the outdoor lambs would be exposed to heat stress.…”
Section: Resultsmentioning
confidence: 99%
“…The higher sulla intake found in this experiment could be related to the more favourable chemical composition observed in legume forage, which was higher in protein and non-structural carbohydrates (270 v. 158 g/kg of DM for sulla and ryegrass, respectively; data not shown in the tables) and lower in structural carbohydrates in comparison with ryegrass. Indeed, it is well established that the degree of synchrony between the rates of fermentation of carbohydrates and degradation of protein in the rumen influences diet selection and intake of ruminants (Kyriazakis and Oldham, 1997). Moreover, Burke et al (2004) suggested that the greater DM intake of sulla forage is linked to the greater ratio of degradable-to-structural carbohydrates, resulting in a faster rate of breakdown in the rumen, and subsequent outflow to the intestine.…”
Section: Resultsmentioning
confidence: 99%
“…Heifer initial response to increased CP intake on days 15 and 16 of the trial, which was decreased intake of tannin solutions, may have been because of short-term disruption of rumen digestion of CP and carbohydrates (Kyriazakis and Oldham, 1997;Reynolds and Kristensen, 2008) which may have stabilized after day 17.…”
Section: Discussionmentioning
confidence: 99%